Polypharmacy and health outcomes among older adults discharged from hospital: Results from the CRIME study. Issue 2 (28th January 2014) - Sganga, Federica; Landi, Francesco; Ruggiero, Carmelinda; Corsonello, Andrea; Vetrano, Davide L; Lattanzio, Fabrizia; Cherubini, Antonio; Bernabei, Roberto; Onder, Graziano
<x xml:space="preserve">Abstract</x> Aim To investigate if older adults using multiple drugs have an increased risk of rehospitalization and mortality after hospital discharge. Methods This was a prospective cohort study carried out in acute care hospitals. The primary outcomes of the study were rehospitalization and mortality within 1 year after discharge from acute care hospitals. The study population was categorized in two groups according to the number of drugs prescribed at hospital discharge: no polypharmacy (<8 drugs) and polypharmacy (≥8 drugs). Results The mean age of 480 participants was 78.6 ± 6.8 years, and half of them (n = 238; 49.6%) were using multiple drugs (≥8 drugs). Overall, 65 out of 242 participants (26.9%) in the no polypharmacy group and 92/238 (39.1%) in the polypharmacy group were rehospitalized (P = 0.004), and 15 out of 242 (6.2%) in the no polypharmacy and 23 out of 238 (9.7%) in the polypharmacy group died during the 1 year follow up (P = 0.16). After adjusting for potential confounders, participants in the polypharmacy group had an increased risk of 1‐year rehospitalization as compared with those in the no polypharmacy group (RR = 1.81, 95% CI = 1.18–2.75). No significant association was observed between mortality and polypharmacy. Conclusions Older persons using multiple drugs are at increased risk of rehospitalization. Further studies are required to assess the impact of programs aimed at reducing polypharmacy on health outcomes. Geriatr Gerontol Int 2015; 15: 141–146.